The impact of digital transformation on the satisfaction of circulation service users at the University of Bengkulu Library - Andi Saputra; Nanik Rahmawati; M. Giatman; Ambiyar Ambiyar (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. This study evaluates user satisfaction with circulation services at the University of Bengkulu Library after the COVID-19 pandemic. The paper aims to understand how technology-based circulation services meet the needs of library users. Research methods. A quantitative approach was adopted by collecting data from 254 valid online questionnaires from active students at the University of Bengkulu. The research instrument integrates the modified LibQUAL+ and End-User Computing Satisfaction (EUCS) models. Data analysis. Data were analyzed using descriptive statistics (mean, standard deviation) and inferential statistics, specifically one-way ANOVA, to assess the influence of demographic variables. Result. The analysis results revealed overall user satisfaction with circulation services in the high category, despite a significant decline in post-pandemic physical book lending transactions. The four dimensions of measurement indicate a high level of satisfaction. However, there is a discrepancy between the information listed on the OPAC and the physical location of the collection, which suggests the need for better guidance in the search and organization of the collection. Conclusion. Integrating the LibQUAL+ and EUCS models has proven effective in evaluating technology-based circulation services. EUCS dimensions, such as Access and Ease of Use, are particularly relevant for measuring performance and aligning the accuracy of OPAC information and physical storage locations.